2013
DOI: 10.1093/jac/dkt270
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of various mobile genetic elements in Enterococcus faecium and Enterococcus faecalis

Abstract: ObjectivesTo determine the fitness effects of various mobile genetic elements (MGEs) in Enterococcus faecium and Enterococcus faecalis when newly acquired. We also tested the hypothesis that the biological cost of vancomycin resistance plasmids could be mitigated during continuous growth in the laboratory.MethodsDifferent MGEs, including two conjugative transposons (CTns) of the Tn916 family (18 and 33 kb), a pathogenicity island (PAI) of 200 kb and vancomycin-resistance (vanA) plasmids (80–200 kb) of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 49 publications
(84 reference statements)
1
82
0
1
Order By: Relevance
“…; Starikova et al. ). This host‐plasmid coevolution could also explain why the cost of the same plasmid is so variable between different bacterial hosts – hosts in which a plasmid has a low fitness cost may have had a longer or more recent history of carrying that type of plasmid.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…; Starikova et al. ). This host‐plasmid coevolution could also explain why the cost of the same plasmid is so variable between different bacterial hosts – hosts in which a plasmid has a low fitness cost may have had a longer or more recent history of carrying that type of plasmid.…”
Section: Discussionmentioning
confidence: 96%
“…; Starikova et al. ). There are also costs of MGE acquisitions where the genetic background was not controlled (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Although a considerable reduction in fitness was observed by newly acquired plasmids and other mobile genetic elements (Starikova et al, 2013; Göttig et al, 2016), some studies showed that carbapenemase-encoding plasmids contributed to low to moderate fitness cost to host (Schaufler et al, 2016; Di Luca et al, 2017). To explore whether bla NDM-5 or mcr-1 plasmid imposed a fitness cost on the host, the growth kinetics were investigated in the transconjugants.…”
Section: Discussionmentioning
confidence: 99%
“…Det er kunnskapshull knyttet til forståelsen av slike kostnader for bakteriene, og hvordan disse kan kvantifiseres og hvordan de påvirkes av kompensatoriske mutasjoner. Slik forståelse er nødvendig for å kunne forutsi i hvilken grad ervervet resistens er reversibel (Johnsen et al, 2009;Starikova et al, 2013;Starikova et al, 2012). Kunnskap om populasjonsstrukturen til mikrober er sentralt også med hensyn på forståelsen av mulige "utvaskingseffekter" hvor repetert tilførsel av konkurrerende bakteriepopulasjoner, f. eks som fôrtilskudd til husdyr, påvirker etablerte resistente populasjoner.…”
Section: Faktorer Som Bidrar Til Opprettholdelse Av Ervervet Resistenunclassified